Analysis of Change in Patient Reported Outcome Measures Following Minimally Invasive Chevron Akin Osteotomies (MICA) in Hallux Valgus Surgery. Issue 1 (January 2022) - Gordon, David; Lewis, Thomas L.; Ray, Robbie
Category: Bunion Introduction/Purpose: There is a need to understand the rate of improvement following minimally invasive chevron akin osteotomies (MICA) for correction of hallux valgus deformity using validated patient reported outcome measures (PROMs) and whether this change is clinically meaningful in order to help counsel patients as to their progress. Methods: Between July 2014 and November 2018, data was prospectively collected from consecutive patients pre-operatively and at 6, 12, and 24 months following MICA. The primary outcome measure was the change in Manchester Oxford Foot and Ankle Questionnaire (MOXFQ) score at each timepoint following MICA. Secondary outcomes include radiographic deformity correction, and exploration of cases where PROMs did not improve following MICA. Results: 190 feet with complete PROM data at each time point, were identified from a cohort of 334 feet undergoing third generation MICA. There was a statistically significant improvement in MOXFQ score for each MOXFQ domain at each time point following MICA although the majority of the improvement was within the first 6 months. 17 feet had worse MOXFQ Index scores at the six month timepoint compared to pre-operatively. Of these feet, 82.4% (n=14) improved over time such that by two years their score had improved compared to their pre-operative score. Conclusion: There is a statistically significant improvement in MOXFQ score at every time point following MICA for hallux valgus. The majority of patients who scores are worse at 6 months following will go on to have improved function compared to their pre-operative state.